Literature Review: Exploring the Relationship Between Gender Cognition and Student Academics - Zhang, Yichi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
In the course of human history, discussion regarding gender differences and sexual roles has never come to an end. In present-day society, cultural influences, together with the “discovered” physiological differences, have contributed to severe gender inequalities and bias that can be perceived in all aspects. Under this distressing situation, education should be an important aspect that must be paid attention to as it is a determining factor of societal development. Based on empirical research, it really should be concerned that the often biased gender cognition may have potentially contributed to educational impairment, for which the disparate attitudes, opinions, and assumptions that people hold about the two genders, based on sufficient empirical research, have strongly influenced students’ academic performance and have further facilitated the formation of inequalities in future learning opportunities, career path, etc.; it is fair to say that these series of connections have gradually formed a negative feedback loop worsening the current inequality situation. This paper will focus primarily on finding the connections between the tendentious beliefs on gender cognition and students’ academics; specifically, empirical research papers regarding how people’s gender cognition may affect different aged students’ academic performance and self-concepts at schools will be reviewed to look for possible relationships.